Discursos de e sobre cegos: pelas veredas da Semiótica - Cavalcante, Maria do Socorro de Araujo (2012)
This thesis studied discourses by and about blind people in the Brazilian and International Popular Literature which previously belonged to the oral tradition and subsequently were collected for writing; as well as texts produced in modern times. To accomplish this, the starting point was the hypothesis that the discourses by and about blind people pertinent to Popular Literature delineate the socially constructed image of the blind subject. The research was guided by the general objective that aimed at analyzing popular texts by and about blind people in the light of theoretical designs of the Greimasian Semiotics at its three levels: fundamental, narrative and discursive, which generate meaning to unravel the systems of values invested by the blind subjects, their beliefs, their world view and their image in society. The analytical assessment was completed by the Cultural Semiotics which verified the anthropogenic areas surrounding human beings. The available corpus consisted of three hundred and eighty-four popular national and international texts produced by blind and not blind poets. This statistical population grouped literary genres of popular expression classified as quatrains, narratives of cordel, arguments or poetries of challenge, songs, poetries, poems, stories and oral novels; among those, seven texts were selected to compose the sample. The analyzed discourses were compiled by the initial letters of the words in the title: Cantador que perdeu a vista (CPV), O cego de Várzea Alegre e o milagre do Cícero (CVAMPC), Os dois cegos e o engraçado (DCE), A luz e a escuridão (LE), Meu caminho é o céu (MCC), Peleja com Zé Pretinho (PCAZP) e A virgem e o cego (VC). The content of the paper is organized into three chapters: the first chapter comprises the Theoretical Study from Signs to Semiotics, the second one outlines the Exhibition of the corpus and the third is the acomplishment of the Semiotic Analysis of discourses by and about blind people. In the end, the results achieved through the appreciation of discourses are presented.